Diagnostic importance of cytochemical and cytoenzymic observations on the blood cells of pig - MEHTA, SURESH; SINGH, ISHWAR; MRIGESH, MEENA (The Indian Journal of Animal Sciences, 2012)
Cytochemical observations based on diagnostic importance of blood cells were carried out on 10 apparently healthy adult pigs. The eosinophils and neutrophils showed positive reactions in the form of pink granules in the cytoplasm when the blood smears were stained with the periodic-acid-Schiff’s stain. The eosinophilic granules stained black when stained with Sudan black B, whereas neutrophil showed very weak to negative reaction with Sudan black B. The granules of basophils showed strong positive reaction and stained metachromatically with toluidine blue. All leukocytes showed negative reaction for acid phosphatase. The neutrophils showed moderately positive reaction in the form of brown granules, when stained for alkaline phosphatase. The granules of eosinophils and basophils showed strong positive reactions for peroxidase and non specific esterase. The neutrophils and eosinophils showed intense positive reactions in the form of blue granules when stained for beta-glucuronidase.